VALIDITY ANALYSIS OF THE SCIENCE PROCESS SKILLS ASSESSMENT INSTRUMENT FOR HIGH SCHOOL STUDENTS ON CHEMISTRY MATERIALS - Faderina Komisia; Maria Benedikta Tukan; Diana Yanni Ariswati Fallo; Gradiana Jenisa Perlita Hale; Geosefina Besi Meta; Petronela Onika Lanmai; Fransiska Eflani; Maria Aloisia Uron Leba (Jurnal Penelitian Pendidikan IPA, 2025)
The assessment of students' science process skills in several senior high schools in Kupang City is still limited to the final learning outcomes, such as written test scores, and does not optimally measure the scientific thinking process that takes place. The assessment instruments used by teachers still tend to measure only cognitive aspects, so that aspects of science process skills are neglected. The assessment instruments used to measure these skills must have content validity so that the assessment results are accurate and reliable. This study aims to analyze the content validity of assessment instruments for science process skills of senior high school students in grades X, XI, and XII. The research method used is content validity through expert judgment. The science process skills assessment instruments were assessed by six expert validators, namely two learning experts, two chemistry experts, and two evaluation experts. The expert assessment data were analysed using Aiken's V. The results showed that the assessment instruments for science process skills of high school students in grades X, XI, and XII were classified as valid with an average V score of 0.74, which means that the assessment instruments are ready and suitable for use by teachers and schools. The assessment instrument meets the content validity criteria and can be used to assess students' skills in the chemistry learning process at school, but it still needs improvement in several aspects and indicators to enhance the overall quality of the instrument.